Biobanking as a research accelerator: the perspectives of medical students and interns at a saudi university - AbuOmar, Leena; Al Eissa, Mariam M.; Tamim, Hani; Abu-Dawas, Sadeq; Yaqinuddin, Ahmed; Alkattan, Khaled (Frontiers in Genetics, 2026)
BackgroundBiobanks play a significant role in the storage of biological samples for medical research, disease diagnosis at an early stage, treatment, and drug development. The research paper evaluates how medical students at Alfaisal University perceive and understand biobanking, as well as their level of ethical awareness. The study is a gap filler in the current literature base, as it reveals information about what Saudi medical students know and believe regarding biobanking.MethodsThe research employed a cross-sectional method where a survey was administered to medical students and interns at Alfaisal University, Saudi Arabia. A self-administered online questionnaire was used to collect the responses. The questionnaire included 30 questions divided into three subgroups: demographic, knowledge of the principle of biobanking, and perception and attitude towards biobanking. The validity of the questionnaire was evaluated in two directions, i.e., an expert review and a pilot test. The latter sample excluded those who were involved in the pilot stage. The sample size consisted of 457 students, with 72.2% being women and 40% being interns.ResultsThe mean of the knowledge scores was 3.93 (SD = 1.63), indicating an average knowledge level. 82.7% of the participants stated that biospecimen donation was a noble activity for society and medical research. 77.7% of the participants advocated for increased resource allocation to biobanking. The dangers of abuse, privacy invasion, and discrimination were brought up, with 81.8% expressing the need for restrictive regulation in medical research. 69.2% of the participants think that a researcher can ensure the interest of the participants, and 4.2% do not believe it is possible. A large proportion of the respondents reported that they would be concerned by the possibility of misuse of the sample (65.2%), confidentiality (64.8%), and discriminatory use (46.2%). Moderate knowledge concerning biobanking (mean = 3.93, SD = 1.63) was observed in the participants, but no significant correlation existed between the knowledge and the desire to contribute biospecimens.ConclusionMedical students at Alfaisal University are moderately informed about biobanking and are generally altruistic, although they also express serious ethical concerns about the utilization and safety of their information. Factual knowledge does not necessarily impact the decision to donate, and ethics, trust and positive attitudes should play a significant role in the encouragement of participation in biobanks. These findings highlight the importance of prioritizing open communication and strong ethical safeguards in biobanking ventures, as well as the integration of specialized biobanking education into medical education. This two-pronged approach is necessary to build trust and equip future medical practitioners with the opportunities to facilitate biobanking efforts in Saudi Arabia.